Sound intentions - McDonald, Peter (Oxford University Press, 2013)
A pioneering stylistic study of major nineteenth-century poets with a special concentration on the ways in which rhyme becomes a mode of meaning.
Includes bibliographical references and index.
Keywords: English poetry; Rhyme.